The neuroprotective effect and possible therapeutic application of xenon in neurological diseases. Issue 12 (29th October 2021) - Zhang, Mengdi; Cui, Yaru; Cheng, Yao; Wang, Qiaoyun; Sun, Hongliu
Abstract: Xenon is an inert gas with stable chemical properties which is used as an anesthetic. Recent in vitro and in vivo findings indicate that xenon also elicits an excellent neuroprotective effect in subanesthetic concentrations. The mechanisms underlying this primarily involve the attenuation of excitotoxicity and the inhibition of N‐methyl‐d ‐aspartic acid (NMDA) receptors and NMDA receptor‐related effects, such as antioxidative effects, reduced activation of microglia, and Ca 2+ ‐dependent mechanisms, as well as the interaction with certain ion channels and glial cells. Based on this strong neuroprotective role, a large number of experimental and clinical studies have confirmed the significant therapeutic effect of xenon in the treatment of neurological diseases. This review summarizes the reported neuroprotective mechanisms of xenon and discusses its possible therapeutic application in the treatment of various neurological diseases.